Risk and protective factors for falls on stairs in young children: multicentre case–control study. Issue 10 (10th December 2015) - Kendrick, D; Zou, K; Ablewhite, J; Watson, M; Coupland, C; Kay, B; Hawkins, A; Reading, R
Abstract : Aim: To investigate risk and protective factors for stair falls in children aged <5 years. Methods: Multicentre case–control study at hospitals, minor injury units and general practices in and around four UK study centres. Cases were children with medically attended stair fall injuries. Controls were matched on age, sex, calendar time and study centre. A total of 610 cases and 2658 controls participated. Results: Cases' most common injuries were bangs on the head (66%), cuts/grazes not requiring stitches (14%) and fractures (12%). Parents of cases were significantly more likely not to have stair gates (adjusted OR (AOR) 2.50, 95% CI 1.90 to 3.29; population attributable fraction (PAF) 21%) or to leave stair gates open (AOR 3.09, 95% CI 2.39 to 4.00; PAF 24%) both compared with having closed stair gates. They were more likely not to have carpeted stairs (AOR 1.52, 95% CI 1.09 to 2.10; PAF 5%) and not to have a landing part-way up their stairs (AOR 1.34, 95% CI 1.08 to 1.65; PAF 18%). They were more likely to consider their stairs unsafe to use (AOR 1.46, 95% CI 1.07 to 1.99; PAF 5%) or to be in need of repair (AOR 1.71, 95% CI 1.16 to 2.50; PAF 5%). Conclusion: Structural factors including having landings part-way up the stairs and keeping stairs in good repair were associated with reduced stair fall injury risk. Family factors including having stair gates, not leaving gates open and having stair carpets were associated with reduced injury risk. If these associations are causal, addressing these factors in housing policy and routine child health promotion could reduce stair fall injuries.